Comparative Study on the Effect of Plant-Based Coagulant on Wastewater Quality: A Systematic Review - Md Amin, Naqibah Solehah; Ahmad, Mazatusziha (Progress in Engineering Application and Technology, 2022)
Indiscriminate disposal of this wastewater (with or without an appropriate level of treatment) can cause water pollution and land pollution. This has a profound effect on the health of living beings apart from the impacts on the abiotic components such as soil and water.  In general, wastewater treatment plants use inorganic coagulants that can be responsible for detrimental effects on water quality on public health due to their over-dosage. Thus, in this study the effectiveness of plant-based coagulants upon coagulation performance were analyzed in terms of qualitative analysis via systematic review. 30 studies related to the effect of plant-based coagulant were identified via PRISMA method. The criteria such as turbidity removal, amount of dosage and pH of water sample after treatment using plant-based coagulant were correlated via content analysis from systematic review. Overall, the findings obtained provide comprehensive information and act as reference on determination which Moringa Oleifera is the best plant-based coagulant based on the performance of removal efficiency (turbidity, COD and BOD) for wastewater treatment.